Evaluation of Staphylococcus aureus Bacteremia: Academic and Community-Based Management Within the Same Health System. (15th March 2017) - Ased, Sumaya; Rayes, Hamza; Dhami, Jaspreet; Amosson, Nick; Fordjour, Akua; Macaraeg, Jeff; Vivekanandan, Renuga; Wilson, Josh; Cabri, Annie; Davids, Michele; Anthone, Jennifer; Cavalieri, Stephen; et al.
Abstract : A nonrandomized, retrospective comparison of Staphylococcus aureus bacteremia between an academic hospital setting (n=53) and a community hospital setting (n=245) within a single healthcare system was performed. Despite infectious disease consultations, S. aureus bacteremia management recommendations based on Infectious Diseases Society of America (IDSA) guidelines were not followed as closely in the community hospital setting. The community hospital setting requires management standardization for patients with S. aureus bacteremia. Infect Control Hosp Epidemiol 2017;38:740–742